Introduction to information science - Bawden, David; Robinson, Lyn, 1962- (Facet Publishing, 2022)
The second edition of this definitive textbook provides an introduction to the library and information sciences, emphasising their philosophical, theoretical, and conceptual foundations. Updated to cover the changing information environment, it is suitable as a text for college and university students, for those beginning research, and for thoughtful practitioners.